2015
DOI: 10.1038/srep11041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and observation of antisite defects in LiNiPO4 nanomaterials

Abstract: Structural studies of high voltage cathode materials are necessary to understand their chemistry to improve the electrochemical performance for applications in lithium ion batteries. LiNiPO4 nanorods and nanoplates are synthesized via a one pot synthesis using supercritical fluid process at 450 oC for 10 min. The X-ray diffraction (XRD) analysis confirmed that LiNiPO4 phase is well crystallized, phase purity supported by energy dispersive spectroscopy (EDS) and elemental mapping by scanning electron transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…This value is reduced to ~0.06 V in the 2 nd cycle onwards, which may be indicative of mitigation of anti-site defects. An in-situ neutron diffraction study has recently revealed that the Li ions in the anti-sites of metal oxide layers are preferentially extracted32. Likewise the small redox peak separation and high reversibility observed in Fig.…”
Section: Resultsmentioning
confidence: 82%
“…This value is reduced to ~0.06 V in the 2 nd cycle onwards, which may be indicative of mitigation of anti-site defects. An in-situ neutron diffraction study has recently revealed that the Li ions in the anti-sites of metal oxide layers are preferentially extracted32. Likewise the small redox peak separation and high reversibility observed in Fig.…”
Section: Resultsmentioning
confidence: 82%
“…This is in agreement with the intralayer intermixing between Li and Sn found in the experiment 27 . Antisite defects have been observed in a variety of other Li ion battery materials during cycling 8,33–37 . The formation enthalpy of Li 2 O via the Li 2 O Schottky-like reaction (relation 5) is a processes that requires an energy of 1.90 eV per defect (refer to Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The lowest intrinsic defect energy process was calculated to be the cation mixing (anti-site) in which Li and Al exchange their atomic positions. This defect was noted in various oxide materials experimentally and theoretically [37][38][39][40][41][42][43][44][45][46][47]. The primary reasons for this defect include experimental conditions for the preparation of as-prepared compounds and cycling of as-prepared materials particularly in battery applications.…”
Section: Crystal Structure Intrinsic Defect Processes and LI Diffusionmentioning
confidence: 98%